(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
One of the main ideas expressing the essence of strategic management is the need to focus the attention of the organization’s management on environmental factors to provide a chance to quickly respond to ongoing changes and modern challenges. Distinctive features of strategic management are: focusing mainly on the problems of the external environment, searching for opportunities in competition, adapting to changes in the environment; long-term orientation; the employee is the foundation of the organization, the source of well-being; the effectiveness of forces is expressed in how timely and accurately the organization is able to respond to new demands from the market and change depending on changes in the environment. The place of strategy in the management of the organization lies in its following features: strategy defines the main directions and ways of strengthening; growth and change due to the concentration of efforts on certain priorities; strategy is the basis for developing strategic plans, projects and programs, as well as the main criteria used to select the most reasonable effective solutions.